PENGEMBANGAN MEDIA BERBANTUAN GEOGEBRA PADA SISTEM PERTIDAKSAMAAN LINEAR-KUADRAT DALAM MENINGKATKAN LITERASI MATEMATIKA SISWA - Dian Kurniati; Fitri Annisa; Randi Pratama Murtikusuma; Didik Sugeng Pambudi; Abi Suwito (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
The purpose of this research is to develop a valid, practical, and effective interactive learning media assisted by GeoGebra. This study used the Thiagarajan (4-D) model which includes four stages, namely defining, designing, developing, and disseminating. The process of the four stages produced an interactive GeoGebra learning media, so students can explore practice questions related to inequalities material independently. The research subjects selected were students of class X Science 2 SMAN Arjasa Jember. The result of this development is a valid interactive learning media assisted by GeoGebra with a very high level of validity, included as practical criteria based on students' scores as media users, and is proven to be effective in improving students' mathematical literacy skills based on the N-Gain from the average pretest and posttest. This interactive learning media assisted by GeoGebra received positive responses from students as an interesting media that support students to understand the material during their sudy.